The Influence of Paylater and Affiliate Features on Consumer Buying Interest in Shopping on the Shopee Aplication - Irma Trimulyawati; Ladina Syafa Sholeha; Adi Setiawan; Tiara Muthiarsih (CV. Media Digital Publikasi Indonesia, 2024)
The paylater feature is a digital payment feature that uses an e- commerce platform, purchasing goods among teenagers is very lacking due to the economic conditions that are currently unstable. The method used in this research is quantitative method. The population in this study was conducted at the unswagati Cirebon campus, level 1-4 management study program as many as 147 respondents. The sampling technique used by researchers is non-probability sampling with purposive sampling technique and data analysis used in this researcher is regression and descriptive analysis then the analysis methods used in this study include validity test, cross tabulation, reliability test, normality test, multicollinearity test, hypothesis testing, path analysis fit model test using SPSS and amos Softwer analysis tools to test the effect of paylater and affiliate features on consumer buying interest. The results of this study indicate that the paylater feature has a positive effect on consumer buying interest, affiliates have an effect on consumer buying interest. Because the validity and reliability test results are less than 0.1362, the normality test is less than 0, 01, the multicoronality test is less than 10, hypothesis testing, the results show that all hypotheses are accepted, because the C.R value is more than 1.98, namely with a C.R value of 7.875 and 11.532 respectively. And the P value also shows the same result if the P value is less than 0.05 or symbolized * (below 0.01), it means that the two hypotheses have a significant effect or are accepted. path analysis fit model test is accepted because the GFT measure shows a P-value of more than 0.05, RMSE less than 0.08, CMIN less than 2.00, GFI less than 0.90, AGFI less than, 0.90, CFI more than 0.90, TLI more than 0.90. So it can be stated that the path analysis model fit test is accepted.